The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3920/bm2018.0179
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve MCC1274 with glycosidic activity enhances in vivo isoflavone bioavailability

Abstract: Polyphenols are plant derived compounds that exert many beneficial health effects to the human host. However, associated health benefits of dietary polyphenol are highly dependent on their intestinal metabolism, bioavailability, and absorption. Bifidobacteria, which represent the key members of gut microbiota, have been suggested to promote gut microbial homeostasis and may be involved in the metabolism of polyphenols. In this study, the capabilities of thirteen Bifidobacterium strains in hydrolysing polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The glucuronic acid allows estrogens to remain in the body and exert their effects, which plays a vital role in the process. It was reported that β-glucuronidases and β-glucuronides produced by the genera Bifidobacterium ( 38 ), Clostridium, and Lactobacillus, and play roles in the de-conjugation/conjugation of estrogens ( 39 ). The bacteria derived from gut microbiome involve in the metabolism of hormones via producing relative enzymes and thus regulate the circulation of sexual hormones in women.…”
Section: Relation Of Microbiota and Pcosmentioning
confidence: 99%
“…The glucuronic acid allows estrogens to remain in the body and exert their effects, which plays a vital role in the process. It was reported that β-glucuronidases and β-glucuronides produced by the genera Bifidobacterium ( 38 ), Clostridium, and Lactobacillus, and play roles in the de-conjugation/conjugation of estrogens ( 39 ). The bacteria derived from gut microbiome involve in the metabolism of hormones via producing relative enzymes and thus regulate the circulation of sexual hormones in women.…”
Section: Relation Of Microbiota and Pcosmentioning
confidence: 99%
“…In the last decade, accumulated evidence suggests gut microbiota, such as Lactobacillus spp., Bacteroides spp., and Bifidobacterium spp, involves in the absorption, metabolism, and bioavailability of polyphenols glycosides ( 7 9 ). For instance, glycosides can be hydrolyzed to bioactive aglycones by β-glucosidases that secreted by bacterial in colon and enable the absorption of polyphenols glycosides ( 8 , 9 ). Bifidobacterium strains show the capacity to enhance the bioavailability of daidzein under dysbiosis conditions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, glycosides can be hydrolyzed to bioactive aglycones by β-glucosidases that secreted by bacterial in colon and enable the absorption of polyphenols glycosides ( 8 , 9 ). Bifidobacterium strains show the capacity to enhance the bioavailability of daidzein under dysbiosis conditions ( 8 ). In addition, antibiotics treatment caused gut dysbiosis was involved in poor bioconversion of daidzin glycoside and polyphenols ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, genus Bifidobacterium spp. is one of the most important gut bacteria that releasing all of the four glycosidases selected in the present study, e.g., β-D-glucosidase [35], β-D-xylosidase [36], α-L-rhamnosidase [37] and β-D-fucosidase [38]. Significant difference of the glycosidase activities were observed among the four glycosidases (i.e., β-D-glucosidase > β-D-xylosidase > β-D-fucosidase > α-L-rhamnosidase), these results were consistent with previous studies, and the differences were probably caused by the composition of gut microbiota [19,39,40].…”
Section: Discussionmentioning
confidence: 99%